Genotypic variation for growth and yield response at two elevated levels of CO2 and three seasons in blackgram (Vigna mungo) - VANAJA, M; SANKAR, G R MARUTHI; MAHESWARI, M; LAKSHMI, N JYOTHI; YADAV, S K; VAGHEERA, P; RAZAK, S K ABDUL; ABRAHAM, BABU; KUMAR, G VIJAY; VENKATESWARLU, B (The Indian Journal of Agricultural Sciences, 2015)
Eighteen blackgram [Vigna mungo (L) Hepper] genotypes were evaluated at three levels of CO2 (390, 550 and 700 ppm) under Open Top Chamber (OTC) condition during summer, rainy and winter seasons to assess the interactive effect of seasons and CO2 levels on the performance of morphological, biomass and yield traits to identify efficient genotype(s). The analysis of variance indicated significant differences among genotypes, CO2 levels and seasons. The interaction of genotypes × CO2 levels, genotypes × seasons and seasons × CO2 levels were also observed significant. The study indicated that performance of the majority of traits improved with both elevated CO2 levels of 550 ppm and 700 ppm in all three seasons; however the magnitude of response of individual traits differed with seasons. Elevated CO2 improved the seed yield of blackgram genotypes by improving pods/plant, seed number and test weight. The improvement of the traits was significantly high in summer and rainy season as compared with winter season. Among the 18 blackgram genotypes evaluated majority of the traits including total biomass and seed yield of LBG 20 check variety and IC398971 performed best in summer over all three CO2 levels; IC436665 in rainy season and IC398971 and IC519805 in winter. At ambient level (390 ppm) the genotype IC343947, at 550 ppm the genotype IC587751 and at 700 ppm the genotype IC436665 recorded superior performance for the majority of the traits over the seasons. The variability in response of blackgram genotypes for CO2 levels and seasons provide a basis to identify suitable traits in developing stable performing varieties for changing climatic conditions.